BIOMARKERS OF NEOVASCULAR ACTIVITY IN AGE-RELATED MACULAR DEGENERATION USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 2 (February 2018) - Al-Sheikh, Mayss; Iafe, Nicholas A.; Phasukkijwatana, Nopasak; Sadda, SriniVas R.; Sarraf, David
Abstract : Purpose: To study the qualitative and quantitative features of choroidal neovascular (NV) membranes in age-related macular degeneration using optical coherence tomography angiography in patients with active and quiescent NV lesions before and after treatment with anti–vascular endothelial growth factor. Methods: Macular optical coherence tomography angiography images were obtained using RTVue XR Avanti with AngioVue. Morphologic features and quantitative measurements of the NV lesion were analyzed using en face projection images. The NV lesion was subdivided into inner segment and outer fringe for further fractal dimension analysis. Results: In a series of 31 eyes, 11 eyes with active NV lesions at baseline and after consecutive follow-up after treatment with anti–vascular endothelial growth factor therapy and 20 eyes with quiescent NV lesions were included in this study. Morphologically, all the quiescent NV lesions versus 63.6% of the active NV lesions demonstrated a prominent central vessel and active leasions demonstrated a greater rate of small vessels branching (82%) and peripheral arcades (82%) than quiescent lesions (30% and 40% respectively) and this was statistically significant. The lesion area and vessel density was not statistically significantly different after treatment or versus quiescent lesions although the latter lesions were reduced in area. Lesion pattern complexity measured by the fractal dimension was statistically significantly lower in the inner part of the lesion after treatment and statistically significantly lower in the total lesion of the quiescent NV compared with the active NV. Conclusion: Optical coherence tomography angiography is a new, noninvasive imaging modality that can be used to perform qualitative and quantitative analyses of NV lesions. In the future, OCT angiography may provide biomarkers of activity and guide the evaluation and treatment and monitoring of neovascularization in age-related macular degeneration. Abstract : The authors evaluated the structural features of active neovascularization before and after treatment versus inactive or quiescent neovascularization secondary to age-related macular degeneration using qualitative and quantitative OCT angiography. Active lesions showed similar morphologic and quantitative features before and after treatment but quiescent lesions differed qualitatively and quantitatively compared with active neovascularization.